Effect of Outsourcing Strategies on the Operational Performance of Small and Medium Scale Enterprises in Ghana - Johnson NSOWAH; Maxwell Agabu PHIRI (Indonesia Strategic Sustainability, 2023)
The study examined the effect of outsourcing on the operational performance of small and medium enterprises (SMEs). Using questionnaires, a descriptive research design was employed with a sample size of 68 SMEs in Sunyani Municipality. The data analysis was based on a mean score and standard deviation using SPSS. The nature of outsourcing recorded in the study was the SMEs outsourcing some of their activities (mean score = 4.47, SD = 0.47), the practice affecting all areas of their operations (mean score = 4.24, SD = 0.47), and specifically internal operations (mean score = 4.17, SD = 0.55). The reasons SMEs in Sunyani practice outsourcing are to free up the company's resources to focus on its core competencies (mean score = 4.41, SD = 0.37), improve its competitive position (mean score = 4.26, SD = 0.41), avoid labour issues (mean score = 4.11, SD = 0.43), reduce cost (mean score = 3.82, SD = 0.52), reduce the risk associated with in-house production (mean score = 3.80, SD = 0.54), and increase efficiency (mean score = 3.75, SD = 0.60). The effects of outsourcing on operations and service delivery are reduced through superior provider performance, and the provider's lower cost structure (mean score = 4.21, SD = 0.43) and existing skills are commercially exploited (mean score = 4.18, SD = 0.47). Therefore, SMEs in Sunyani are encouraged to continue with their outsourcing practices. However, further study is recommended on the factors and challenges affecting outsourcing among Ghanaian companies.